Descriptions of new species of the genera Camptochaeta Hippa & Vilkamaa and Corynoptera Winnertz (Diptera, Sciaridae) from the Holarctic - Vilkamaa, Pekka; Menzel, Frank (Zootaxa, 2017)
Six species of the genus Camptochaeta Hippa & Vilkamaa, 1994 and four of the genus Corynoptera Winnertz, 1867 from the Holarctic region are newly described and illustrated: Camptochaeta chilkatensis sp. n. (USA: Alaska), C. curtipilosa sp. n. (USA: Colorado), C. exquisita sp. n. (USA: Oregon), C. fitzgeraldi sp. n. (USA: Oregon), C. fulvistylata sp. n. (Canada: British Columbia), C. pertenuis sp. n. (Russia: Krasnodarsk region), Corynoptera bocheri sp. n. (Greenland; Canada: Quebec), C. hyperborea sp. n. (Russia: Krasnodarsk region), C. hystricina sp. n. (RUSSIA: Krasnodarsk region) and C. tenuichaeta sp. n. (Russia: Krasnodarsk region).